Construcción de escenarios cognoscitivos basados en tendencias cualitativas - Scheel, Carlos (1993)
This study offers a model for the construction of cognitive scenarios based on a systemic approach, and on the identification, tracking and projection of qualitative trends. The model is part of the exploratory strategy of a flexible knowledge-bases decision support system, designed by the author himself to handle unstructured environments. The concept of cognitive scenarios is based on qualitative trends and provides an effective and functional frame of reference for decision makers who need to project complex situations over long periods of time and in which many factors affect the behavior of the results. It is concluded that cognitive scenarios generate a series of intuitive behavioral patterns able to support strategies that, in general, are not able to be managed by conventional descriptive or normative models. In addition, cognitive scenarios provide a stronger support to develop strategic policies for decision makers.